2008
DOI: 10.1002/art.24125
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex on the chondrogenic potential of muscle‐derived stem cells: Implications for cartilage regeneration and repair

Abstract: Conclusion. Our findings demonstrate that sex influences the chondrogenic differentiation and articular cartilage regeneration potential of MDSCs. Compared with female MDSCs, male MDSCs display more chondrogenic differentiation and better cartilage regeneration potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…[8][9][10] MDSCs are known to exhibit sex differences in muscle regeneration, as well as chondrogenic and osteogenic differentiation both in vivo and in vitro. [11][12][13] MDSCs isolated from female mice have a higher regeneration efficiency when transplanted into mdx or mdx/SCID mice, a dystrophindeficient animal model of muscular dystrophy. In mdx mice, a significant effect of host sex was also seen, with female hosts exhibiting higher regeneration.…”
mentioning
confidence: 99%
“…[8][9][10] MDSCs are known to exhibit sex differences in muscle regeneration, as well as chondrogenic and osteogenic differentiation both in vivo and in vitro. [11][12][13] MDSCs isolated from female mice have a higher regeneration efficiency when transplanted into mdx or mdx/SCID mice, a dystrophindeficient animal model of muscular dystrophy. In mdx mice, a significant effect of host sex was also seen, with female hosts exhibiting higher regeneration.…”
mentioning
confidence: 99%
“…In vivo, at 4, 12, and 24 weeks post-operative, the muscle derived MSC and chondrocyte groups were similar and superior to the gel control group. Following this study, the same group also demonstrated that sex influences chondrogenic differentiation and cartilage regeneration potential, with male muscle derived MSCs superior over female [68]. To understand muscle derived MSCs further, Li et al [69], isolated both fascia derived cells from the gluteus maximus muscle fascia and muscle derived cells from the muscle body of rats.…”
Section: Musclementioning
confidence: 85%
“…Muscle-derived MSC has been investigated as a cell source [74], and potentials of other sources such as placenta [75], amnion [76], umbilical cord blood [77], and ear elastic cartilage [78] have been tested in previous in vitro and animal studies.…”
Section: Other Cell Sourcesmentioning
confidence: 99%